How severe will the growth slowdown in China caused by the structural change be? – An evaluation based on experiences from Japan and South Korea - Michael Murach; Helmut Wagner (University of Hagen, Center for East Asia Macro-economic Studies (CEAMeS), 2017)
China has been growing at high rates during the previous three decades. The current process of rebalancing from an investment- and manufacturing-led growth model towards a consumption- and service-led model is associated with decreasing growth rates. We show that China's current state of structural change in terms of sectoral employment shares is similar to the historical developments in Japan and South Korea. We derive plausible scenarios for future growth rates in China and (by isolating the allocation effect, i.e. the pure effect of structural change) look at the effects of tertiarization on economic growth in China for the period 2016 until 2030 by applying a simple simulation study.
urn:nbn:de:hbz:708-dh4653
Keywords: O1; O4; P5; 330; structural change; China; South Korea; Japan; economic development; tertiarization; rebalancing